Pengaruh Konsumsi Susu Sapi Terhadap Penurunan Intensitas Nyeri Dismenore Primer Pada Siswi Jurusan Keperawatan Di SMKN 2 Malang - Febriani, Devi; Ariani, Dewi; Kusumastuty, Inggita (Journal of Issues in Midwifery, 2018)
Primary dysmenorrhea is a common gynecological disorder among adolescents females without pathological abnormalities. Primary dysmenorrhea usually begins two days before menstruation or during menstruation and lasts up to 48-72 hours. This is due to high levels of prostaglandins that cause contraction in the myometrium. The incidence of dysmenorrhea in Indonesia is 64.25%, which 54.89% has primary dysmenorrhea while 9.36% has secondary dysmenorrhea. In principle there are two therapies for treatment of primary dysmenorrhea that is pharmacological and non-pharmacological. Cow milk is a food that containing high calcium and can be used as one of the non-pharmacological therapy to reduce pain intensity of primary dysmenorrhea. This study aims to determine the influence of cow milk consumption to decrease the pain intensity of primary dysmenorrhea in students of nursing department at SMKN 2 Malang. The research design used was true experiment with pre test-post test with control group design. The sample in this study were 21 people and divided into three groups taken by simple random sampling. The results showed that there was a difference of decrease pain intensity in three groups using One Way Anova test with p value 0.000 (p <0.005). The optimal dose can decrease pain intensity of primary dysmenorrhea is cow milk with 1000 mg calcium which has the highest pain delta value of 4.57 compared with experimental group II and control group. So it can be concluded that the higher value of the delta pain then the greater the dose effect given to decreased pain intensity of primary dysmenorrhea.